Spanish perspectives on Chicano literature : literary and cultural essays - Rosales, Jesús, 1955-; Fonseca, Vanessa; Lomelí, Francisco A., 1947- (Global Latin/o Americas, 2017)
Spanish Perspectives on Chicano Literature and Culture: Literary and Cultural Essays explores how Spanish literary critics from the U.S. and Spain view and study Chicano literature and culture, and reflects on Chicano literature's literary place in 21st century America and its transnational aspirations.